Adaptation and Validation of the Mental Health Continuum Long Form (MHC-LF) in Indonesia: A Psychometric Analysis - Sari, Novita; Inskandarsyah, Aulia; Purwono, Urip (Psychocentrum Review, 2023)
The study aims to adapt and validate the MHC-LF in Indonesia. The sample used was 315 participants (29 client group and 286 general group. Psychometric property analysis was carried out, including item analysis, reliability estimation using test-retest and internal consistency, and collecting validity evidence based on test content, internal structure, and relationships with other variables. The results showed that psychological well-being item number 10 and social well-being number 3 had insignificant loading factor values. MHC-LF reliability is high, with r= 0.85-0.94. This shows that the score produced by the MHC-LF is stable over time, and the items that compose it have internal consistency and are unidimensional. The expert panel judgment provides evidence that all MHC-LF items are relevant to measured aspects. Confirmatory factor analyses confirmed the three-factor model of emotional, psychological, and social well-being. MHC-LF is positively correlated with WEMWBS and negatively correlated with BDI-II. The difference in the mean scores of each subscale and the total significantly differed between the general and client groups. The validity evidence proves that the MHC-LF is a measuring tool that measures subjective well-being. The systematic judgmental scale provides evidence that the measurement tool for the translation results is equivalent to the original version.